The digital dilemma : intellectual property in the information age (National Academy Press, 2000)
Imagine sending a magazine article to 10 friends-making photocopies, putting them in envelopes, adding postage, and mailing them. Now consider how much easier it is to send that article to those 10 friends as an attachment to e-mail. Or to post the article on your own site on the World Wide Web. The ease of modifying or copying digitized material and the proliferation of computer networking have raised fundamental questions about copyright and patent--intellectual property protections rooted in the U.S. Constitution. Hailed for quick and convenient access to a world of material, the Internet also poses serious economic issues for those who create and market that material. If people can so easily send music on the Internet for free, for example, who will pay for music? This book presents the multiple facets of digitized intellectual property, defining terms, identifying key issues, and exploring alternatives. It follows the complex threads of law, business, incentives to creators, the American tradition of access to information, the international context, and the nature of human behavior. Technology is explored for its ability to transfer content and its potential to protect intellectual property rights. The book proposes research and policy recommendations as well as principles for policymaking.